How it's done: search tools and techniques for major bibliographic databases. (2nd May 2021) - Holland, Matt; Dutton, Michelle; Glover, Steve
Abstract : This article explains how to write an effective search plan using simple steps. The article takes you through the tools and techniques that are widely used in major bibliographic databases such as MEDLINE and CINAHL to conduct searches. These include Boolean logic, truncation and wildcards, in-field searching, proximity operators, limits and subject thesauri. Each process is illustrated with an example to help you apply them to your own searches. The process of using these tools and techniques to either narrow (find fewer results) or broaden (find more results) is described and summarised in an easy-to-use table.